LIGHT AND WELLBEING: EVALUATING ARTIFICIAL, NATURAL, AND AUTOMATED LIGHTING SYSTEMS IN LAHORE’S WORK ENVIRONMENTS - Nabiha Saleem; Umer Mahboob Malik; Amna Iqbal (Spectrum of Engineering Sciences, 2025)
In today’s world, where conversations around energy efficiency and sustainability are becoming increasingly urgent due to environmental changes and limited resources, it's essential for us—especially as designers and professionals—to consider the role we play in shaping a better future. One of the areas where we can make a real difference is through the way we design and use lighting in our office spaces. Lighting doesn’t just affect energy bills—it impacts how people feel, work, and interact in a space. Unfortunately, many offices still lack access to natural light, even in areas where people spend most of their day. This doesn’t just lead to higher energy consumption; it also affects the experience of the people working there, both mentally and physically. This paper takes a closer look at how natural light, artificial lighting, and automation are being used in office buildings around Lahore. By visiting actual spaces, reviewing case studies, and diving into existing research, the study explores what strategies are being used and whether architects are working hand-in-hand with electrical engineers to make lighting smarter and more energy-efficient. It also looks at whether automation is helping reduce energy use and how much user experience is being considered in these decisions. Since lighting has a direct effect on how people feel and perform at work, this study also gathers feedback from users to understand what is working and what is not. It highlights the reasons behind high energy costs and offers suggestions to improve how we approach lighting in offices. Ultimately, it’s not just about saving energy—it’s about creating spaces that support people and help them thrive.